PRODUCTION DEVELOPMENT EVALUATION OF PLANT COMMODITIES ON SLOVAKIAN AGRARIAN MARKET - Rovný, Patrik; Lančarič, Drahoslav; Savov, Radovan (Acta Scientiarum Polonorum. Oeconomia, 2013)
Market liberalization and influence of the foreign competition were evident mainly in reductions of the areas with cereals, sugar beat and potatoes. In the case of sugar, there was mainly the influence of the reformation of sugar regimen by reducing the number of sugar beat processors. The year 2009 and also the year 2010 in terms of weather were very difficult for the farmers. Intensive rainfalls in Spring and very hot and dry weather in Summer affected all the plant production in negative way. The reasons for the price increase or decrease of commodities in the EU are as follows: cereals reserves, structural changes in the offer and demand, increase in demand on the Asian market, increase in biofuel production, protectionism business policy, currency development, low food production productivity in Africa and in other developing countries and climatic effects mainly in Europe (in the countries where cereals are mainly grown).